Flipped Classroom Learning: A Current Issue in English Language Teaching in Pandemic-Era as Perceived by Lecturers - Eka Sustri Harida; Jufrizal Jufrizal; Sojuangon Rambe (State Institute of Islamic Studies Imam Bonjol Padang, 2022)
The current method of teaching English in today's era is online learning; this condition occurs because of the pandemic era in all countries in the world, including Indonesia. Teaching English should be done at least by using blended learning systems; one of them is by using flipped classroom learning. Unfortunately, many teachers and students in some areas were not ready to face it. This study aims to determine the lecturers' perception of flipped classroom learning. This research was conducted through a mixed method using a questionnaire and interview to obtain data about lecturers' perceptions of flipped classroom learning. Based on the results, it is known that lecturers have a positive perception of flipped classroom learning, and they think that a new era in teaching must be followed. They are ready to face the industrial era with this kind of learning and are ready to provide themselves to become lecturers who are able to use technology, especially to follow the current era of teaching, not only in the Covid-19 era but also in the normal condition. This study recommends further research of the effect of online learning, specifically for flipped classroom learning, on the students' competencies or on the lecturers' professionalism.